Eﬃcacy of IV Ketamine in Refractory/Super-Refractory Status Epilepticus: A Systematic Review and Meta-Analysis - Abhijit Vijay, Lele; Alex, Raquer; Jorge, Mejia-Mantil; Samuel Tsan, Ern Hung; Gentle Sunder, Shrestha; Victor, Lin; Samuel Neal, Blacker; Sean, Marinelli; Peter Chee Seong, Tan; Sarah, Wahlster; Andres, Gempeler (American Academy of Neurology, 2026)
Background and Objectives Intravenous ketamine is increasingly used for refractory and super-refractory status epilepticus(RSE/ SRSE), yet its efficacy and optimal use remain uncertain. We therefore aimed to synthesize the available evidence to quantify the effectiveness of ketamine in achieving seizure cessation and to explore differences in treatmentcharacteristics between patients who respond and those who do not. Methods We conducted a systematic review and meta-analysis to estimate the pooled seizure cessation rate associated with intravenous ketamine. Secondary analyses compared ketamine initiation timing, dosing, and infusion duration between patients who achieved seizure cessation (responders) and those who did not (nonresponders).